A Model Determining Purchase Intention of Halal Skincare Products Amid The Boycott Movement: The Mediating Role of Perceived Influence - Edy Yulianto Putra; Cherllyn Sepvinin; Listia Nurjanah (Media Ekonomi dan Manajemen, 2026)
The resurgence of consumer boycott movements against multinational brands following global geopolitical conflicts has reshaped purchasing behavior in Muslim-majority markets. This study examines the determinants of purchase intention toward halal skincare products in the context of a boycott movement. Drawing on the Stimulus–Organism–Response (SOR) framework, it investigates the effects of interactional factors, audience characteristics, sponsored marketing, and consumer attitudes on purchase intention, with perceived influence serving as a mediating variable. A quantitative explanatory research design was employed using a cross-sectional survey of 466 skincare consumers in Batam City, Indonesia. Data were collected through a structured questionnaire using validated measurement scales and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that interactional factors, audience characteristics, sponsored marketing, and consumer attitudes have significant positive effects on purchase intention, both directly and indirectly through perceived influence. Among these variables, perceived influence emerges as the strongest determinant of purchase intention. The study underscores the importance of leveraging social interaction, influencer-based marketing, and value-congruent communication to strengthen local halal skincare brands amid ongoing socio-political disruptions.